Child custody and domestic violence a call for safety and accountability - Jaffe, Peter G.; Lemon, Nancy K. D., 1953-; Poisson, Samantha E.; Sage eBooks (Thousand Oaks, Calif. ; London : SAGE, 2003)
Jaffe, Lemon and Poisson draw on evidence from countries where legislation makes it mandatory for courts to examine the impact of domestic violence on child witnesses before custody or visitations decisions are made.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Custody of children; Family violence; Family violence -- Law and legislation; Electronic books